Novel strategy to elevate solid state fermentation to produce alkilophilic endoglucanase using date waste feedstocks and peapod extract based nutrient media and expired probiotic strain: Application in fermentable sugar production - Bahkali A.H.; Syed A.; Elgorban A.M.; Abdel-Wahab M.A.; Srivastava N.; Gupta V.K. (My University, 2025)
Solid waste generation and its impactful management are among the most raised environmental concerns seeking sustainable alternatives in the form of value addition. In this study, a novel strategy has been presented towards enhanced bacterial endoglucanase (EG) production under solid state fermentation (SSF). The EG was produced using the waste probiotic juice of the bacteria Lactobacillus casei strain Shirota on a substrate of waste date pulp and seeds in co-fermentation mode. Additionally, peapod extract has been applied as a nutrient medium to maintain moisture in place of commercial media in SSF. Further, for enhancement in enzyme production, the impact of incubation temperature and pH of the SSF medium have been studied to obtain optimum enzyme activity. Under optimum conditions, bacteria produced 17.2 U/mL EG at a temperature of 37 °C and a pH of 8.0. The raw EG showed pH and thermal stability up to 5 h at 60 °C and pH 8.0. Furthermore, the enzymatic hydrolysis of date pulp released 67.71 g/L fermentable glucose obtained in 24 h of the reaction at 60 °C and pH 8.0. This work may have great significance in the areas of solid waste management and microbe-mediated value addition of waste biomass in the context of hydrolytic enzyme production for biorefinery applications. © 2024